2014
DOI: 10.1016/j.conb.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Hypocretin (orexin) neuromodulation of stress and reward pathways

Abstract: Hypocretin (also known as orexin) is a peptide neuromodulator that is expressed exclusively in the lateral hypothalamic area and plays a fundamental role in wakefulness and arousal. Chronic stress and compulsive drug-seeking are two examples of dysregulated states of hyperarousal that are influenced by hypocretin transmission throughout hypothalamic, extended amygdala, brainstem, and mesolimbic pathways. Here, we review current advances in the understanding of hypocretin's modulatory actions underlying conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 54 publications
2
50
1
Order By: Relevance
“…Consistent with this, intracerebroventricular administration of orexin A induces anxiety-like effects in several behavioral models of anxiety [93]. The existence of reciprocal interactions between orexin and CRF neurons [94] suggests that the orexin system is an important component of the pathways contributing to the physiological CRF-mediated behaviors that occur in response to stressful situations [95]. Dysregulation of stress responses could lead to the development of different anxiety disorders, which might be influenced by the activity of the orexin system, as described in the present review.…”
Section: Stressmentioning
confidence: 67%
“…Consistent with this, intracerebroventricular administration of orexin A induces anxiety-like effects in several behavioral models of anxiety [93]. The existence of reciprocal interactions between orexin and CRF neurons [94] suggests that the orexin system is an important component of the pathways contributing to the physiological CRF-mediated behaviors that occur in response to stressful situations [95]. Dysregulation of stress responses could lead to the development of different anxiety disorders, which might be influenced by the activity of the orexin system, as described in the present review.…”
Section: Stressmentioning
confidence: 67%
“…As outlined above, orexin neurons signal at a number of target structures to regulate drug seeking, including VTA [20, 30, 71, 102, 103], PVT [128, 131, 132], and other reward and motivation-related targets [12, 186]. Early work revealed that lateral (LH/PFA) orexin neurons preferentially projected to VTA in rats [187], although orexin neuron projections to VTA in mice appear to originate from both medial and lateral subdivisions [188].…”
Section: Functional Heterogeneity Of Orexin Neurons: a Medial/latermentioning
confidence: 99%
“…There are studies suggesting that nesfatin-1 and orexin-A may be related to many disorders in addition to appetite (10,11,16,37). Moreover, orexin-A has pleiotropic effects, including increasing body temperature, heart rate, and blood pressure by stimulating the sympathetic nervous system (9,38).…”
Section: Orexin-a and Nesfatin-1 In Hyperthyroidismmentioning
confidence: 99%
“…It has been suggested that orexin-A increases both food intake and energy expenditure to prevent weight gain (5). Many publications have shown that orexin-A is related to sleep-wakefulness, arousal, energy balance, narcolepsy, glucose metabolism, gastric ulcers, and thermogenesis (4,(6)(7)(8)(9)(10)(11). The results of animal studies that investigated the relationship of orexin-A with the thyroid axis are contradictory (4,12,13).…”
Section: Introductionmentioning
confidence: 99%